Microalgal hydrogen production research. (10th August 2016) - Eroglu, Ela; Melis, Anastasios
Abstract: Microorganisms can produce hydrogen biologically, with species ranging from photosynthetic and fermentative bacteria to green microalgae and cyanobacteria. In comparison with the conventional chemical or physical hydrogen production methods, biological processes demonstrate several advantages by operating at ambient pressure and temperature conditions, without a requirement for the use of precious metals to catalyze the reactions. In addition to using cellular endogenous substrate from which to extract electrons for H2 -production, a number of green microalgae are also endowed with the photosynthetic machinery needed to extract electrons from water, the potential energy of which is elevated by two photochemical reactions prior to reducing protons (H + ) for the generation of molecular hydrogen (H2 ). Sunlight provides the energy for the microalgal overall strongly endergonic reaction of H2 O-oxidation, electron-transport, and H2 -production. Thanks to a substantial amount of research, a number of diverse experimental approaches have been developed and applied to establish and improve sustainable production of hydrogen. This review summarizes and updates recent developments in microalgal hydrogen production research with emphasis on new trends and novel ideas practiced in this field.